High serum immunoglobulin G and M levels predict freedom from adverse cardiovascular events in hypertension: a nested case-control substudy of the Anglo-Scandinavian Cardiac Outcomes Trial - Khamis,RY; Hughes,AD; Caga-Anan,M; Chang,CL; Boyle,JJ; Kojima,C; Welsh,P; Sattar,N; Johns,M; Sever,P; Mayet,J; Haskard,DO (EBioMedicine, 2016)
Aims: We aimed to determine whether the levels of total serum IgM and IgG, together with specific antibodies against malondialdehyde-conjugated low-density lipoprotein (MDA-LDL),can improve cardiovascular risk discrimination.Methods and Results: The Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) randomized 9098 patients in the UK and Ireland into the Blood Pressure-Lowering Arm. 485 patients that had cardiovascular (CV) events over 5.5 years were age and sex matched with 1367 controls. Higher baseline total serum IgG, and to a lesser extent IgM, were associated with decreased risk of CV events (IgG odds ratio (OR) per one standard deviation (SD) 0.80[95% confidence interval, CI 0.72,0.89], p<0.0001; IgM 0.83[0.75,0.93], p=0.001), and particularly events due to coronary heart disease (CHD) (IgG OR 0.66 (0.57,0.76); p<0.0001, IgM OR 0.81 (0.71,0.93); p=0.002). The association persisted after adjustment for a basic model with variables in the Framingham Risk Score (FRS) as well as following inclusion of C-reactive protein (CRP) and N-terminal pro-B-type natriuretic peptide (NtProBNP). IgG and IgM antibodies against MDA-LDL were also associated with CV events but their significance was lost following adjustment for total serum IgG and IgM respectively. The area under the receiver operator curve for CV events was improved from the basic risk model when adding in total serum IgG, and there was improvement in continuous and categorical net reclassification(17.6% and 7.5% respectively) as well as in the integrated discrimination index.Conclusion: High total serum IgG levels are an independent predictor of freedom from adverse cardiovascular events, particularly those attributed to CHD, in patients with hypertension.